Valorization of animal waste proteins for agricultural, food production, and medicinal applications - Boboua, Stopira Yannick Benz; Wen, Qingmei; Zhang, Lei; Chen, Yilu; Yu, Jingmou; Chen, Pu; Sun, Yong; Zheng, Tao (Frontiers in Sustainable Food Systems, 2024)
Introduction Animal waste proteins have been increasing in the past decade, along with consumer demands. Their huge volume and the environmental issues caused by improper treatment probably pose a massive threat to human health. These animal waste proteins contain many valuable bioactive peptides and can be used not only as nutrient substances but also as primary functional ingredients in many industries, including agriculture, food, and pharmaceuticals. However, the advancement of the value-added application of animal waste proteins within the past 10 years has not been elucidated yet. In this regard, this paper scrutinized the studies on the applications of hydrolysates and peptides from animal waste proteins throughout the last decade, hoping to display a whole picture of their value-adding applications. Methods The Web of Science and Google Scholar were searched from January 1, 2013, to December 12, 2023. This review included field trials, in vitro and in vivo assays, and in silico analysis based on literature surveys or proteolysis simulation. The quality of the included studies was evaluated by Journal Citation Reports, and the rationality of the discussion of studies included. Results Numerous studies were performed on the application potential of hydrolysates and peptides of animal waste proteins in agricultural, food, and medicinal industries. Particularly, due to the nutritional value, safety, and especially competitive effects, the peptide with antioxidant, antimicrobial, antihypertensive, antidiabetic, or antithrombotic activities can be used as a primary functional ingredient in food and pharmaceuticals. Discussion These value-added applications of animal waste proteins could be a step towards sustainable animal by-products management, and simultaneously, open new avenues in the rapid development of nutraceuticals and pharmaceuticals. However, further studies on the bioavailability and structure-activity relationship are required to verify their therapeutic effects.